2014
DOI: 10.1109/tit.2014.2331344
|View full text |Cite
|
Sign up to set email alerts
|

Recursive Robust PCA or Recursive Sparse Recovery in Large but Structured Noise

Abstract: Abstract-This work studies the recursive robust principal components analysis (PCA) problem. If the outlier is the signalof-interest, this problem can be interpreted as one of recursively recovering a time sequence of sparse vectors, St, in the presence of large but structured noise, Lt. The structure that we assume on Lt is that Lt is dense and lies in a low dimensional subspace that is either fixed or changes "slowly enough." A key application where this problem occurs is in video surveillance where the goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
198
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(200 citation statements)
references
References 40 publications
2
198
0
Order By: Relevance
“…However, foreground objects typically occupy contiguous regions and move in a correlated fashion resulting S being sparse as well as low rank. As we observed in [9,10,11], PCP would fail if the support size of S is not small and S has low rank. To address this problem, we introduced an online approach in [9] which we later called Recursive Projected Compressive Sensing (ReProCS) in [10,11].…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, foreground objects typically occupy contiguous regions and move in a correlated fashion resulting S being sparse as well as low rank. As we observed in [9,10,11], PCP would fail if the support size of S is not small and S has low rank. To address this problem, we introduced an online approach in [9] which we later called Recursive Projected Compressive Sensing (ReProCS) in [10,11].…”
Section: Introductionmentioning
confidence: 64%
“…This work designed and evaluated ReProSMR, which is a modification of our earlier work [9,10,11]. We showed that ReProSMR has excellent performance for a real-time video layer separation problem and the performance is better than many of the state-of-the-art algorithms from recent work.…”
Section: Resultsmentioning
confidence: 98%
“…Even for offline applications, a recursive solution is typically faster than a batch one. In [43], we studied a simple modification of the original ReProCS idea and obtained a performance guarantee for it. In recent work [22,39,40,43], we introduced a novel solution approach, called Recursive Projected Compressive Sensing (ReProCS), which recursively recovered S t and L t at each time t. Moreover, as we showed later in [31,32], it can also provably handle correlated support changes significantly better than batch approaches because it uses extra assumptions (accurate initial subspace knowledge and slow subspace change).…”
Section: Related Workmentioning
confidence: 99%
“…Recently, several algorithms have been proposed to address the online subspace estimation problem from incomplete observations [14][15][16][17][18][19][20]. The GROUSE algorithm [14] uses rankone updates of the estimated subspace on the Grassmannian manifold.…”
Section: Related Workmentioning
confidence: 99%
“…More recently, the GRASTA algorithm [16], or robust GROUSE, also uses updates on the Grassmannian manifold using a robust 1 -norm cost to recover from outliers in the observations. Other robust online PCA techniques include recursive projection in ReProCS [17], bilinear decomposition [18], and adaptive projected subgradient STAPSM [19]. These algorithms either do not handle missing data or require relatively accurate initial estimates of the target subspace.…”
Section: Related Workmentioning
confidence: 99%